2019
DOI: 10.1002/etc.4543
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Effects of the Beta‐Adrenergic Agonist Salbutamol in Fish: Supporting Evidence for the Fish Plasma Model

Abstract: The fish plasma model (FPM) predicts the fish blood plasma concentration of a pharmaceutical from the water concentration to which the fish is exposed and compares it with the human therapeutic plasma concentration (HtherPC) with the postulate that no adverse toxic effects occur below the HtherPC. The present study provides several lines of evidence supporting the FPM for the beta‐adrenergic agonist salbutamol, a small cationic molecule at ambient pH. Salbutamol exhibited very low acute toxicity to early and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Human and veterinary pharmaceuticals are biologically active compounds with concentrations in global freshwater environments being measured at the pg−μg/L range and accumulation in biota being observed. , This raises concerns about the effect these compounds may have on aquatic organisms because many human drug targets are evolutionarily conserved in fish and aquatic invertebrates. Adverse effects have been observed for a number of drugs when internal concentrations in fish exceed the human therapeutic plasma concentrations, for example, ethinyl oestradiol, fluoxetine, , glucocorticoids, ibuprofen, propranolol, and salbutamol . Identification and characterization of environmental risks posed by chemicals currently involve lengthy and costly acute and chronic fish toxicity studies, and there is a need to develop alternative methods, whether computational such as QSARs or in vitro techniques. , This is extremely pertinent to pharmaceuticals because there are over 11,000 small molecule drugs and approximately 2500 approved (), most of which are legacy compounds with little environmental impact data …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human and veterinary pharmaceuticals are biologically active compounds with concentrations in global freshwater environments being measured at the pg−μg/L range and accumulation in biota being observed. , This raises concerns about the effect these compounds may have on aquatic organisms because many human drug targets are evolutionarily conserved in fish and aquatic invertebrates. Adverse effects have been observed for a number of drugs when internal concentrations in fish exceed the human therapeutic plasma concentrations, for example, ethinyl oestradiol, fluoxetine, , glucocorticoids, ibuprofen, propranolol, and salbutamol . Identification and characterization of environmental risks posed by chemicals currently involve lengthy and costly acute and chronic fish toxicity studies, and there is a need to develop alternative methods, whether computational such as QSARs or in vitro techniques. , This is extremely pertinent to pharmaceuticals because there are over 11,000 small molecule drugs and approximately 2500 approved (), most of which are legacy compounds with little environmental impact data …”
Section: Introductionmentioning
confidence: 99%
“…4−7 Adverse effects have been observed for a number of drugs when internal concentrations in fish exceed the human therapeutic plasma concentrations, 8 for example, ethinyl oestradiol, 9 fluoxetine, 10,11 glucocorticoids, 12−15 ibuprofen, 16 propranolol, 17 and salbutamol. 18 Identification and characterization of environmental risks posed by chemicals currently involve lengthy and costly acute and chronic fish toxicity studies, 19 and there is a need to develop alternative methods, whether computational such as QSARs 20 or in vitro techniques. 21,22 This is extremely pertinent to pharmaceuticals because there are over 11,000 small molecule drugs and approximately 2500 approved (https://www.drugbank.ca/stats), most of which are legacy compounds with little environmental impact data.…”
Section: Introductionmentioning
confidence: 99%
“…However, greater trust in a (potentially improved) FPM model would be required to defend a threshold of, e.g., 0.01 instead of 0.001 for PEC/TWC. Experimental studies have demonstrated that the FPM (an in silico tool) provides reasonably reliable predictions of blood plasma concentrations of APIs in exposed fish, , even for small cationic molecules that fall outside the applicability domain of the original model . Data derived from in vitro models, e.g., cultured fish gill cells or in silico tools modeling passive transport across membranes, may help to confirm or rebut the assumption of relevant uptake into fish and thereby inform on the reliability and plausibility of a predicted TWC.…”
Section: Refining the Decision Using In Silico Tools Or In Vitro Modelsmentioning
confidence: 99%
“…Experimental studies have demonstrated that the FPM (an in silico tool) provides reasonably reliable predictions of blood plasma concentrations of APIs in exposed fish, 30 , 31 even for small cationic molecules that fall outside the applicability domain of the original model. 32 Data derived from in vitro models, e.g., cultured fish gill cells 33 or in silico tools modeling passive transport across membranes, 34 may help to confirm or rebut the assumption of relevant uptake into fish and thereby inform on the reliability and plausibility of a predicted TWC. In silico prediction models of bioconcentration in fish e.g, refs ( 35 37 ), eventually including consideration of metabolism, 38 may also be useful as supporting evidence for TWC.…”
Section: Refining the Decision Using In Silico Tools Or In Vitro Modelsmentioning
confidence: 99%
“…Possible health impacts from longterm exposure to pharmaceutical β-agonists through drinking water have been well hypothesized [5], and subsequent studies determined their effects on living species as hazardous to aquatic life and people [20] [25]. Higher concentrations of β-agonist in fish plasma are linked to human pharmacological effects [26]. While frequent reports of their occurrences in our environmental waters raises more concerns [27] [5].…”
Section: Figure 1 Terbutaline Modelmentioning
confidence: 99%